EFFECT OF IRON OVERLOAD AND IRON CHELATORS ON ANTI-MÜLLERIAN HORMONE LEVEL IN EGYPTIAN FEMALE PATIENTS WITH TRANSFUSION DEPENDENT β-THALASSEMIA - ALI EL-DESOUKY, MOHAMED; EL-SAYED MOHAMED, MERVAT; ABDEL-AZIZ, SAMIR MOSTAFA; NOURELDIN, AMAL MAHMMED; EL-ADHAM, EITHAR KAREM; SAYED HAMED, NOHA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This work aims to determine the effect of iron overload on serum anti-müllerian hormone (AMH) levels in females subjected to transfusion-dependent β-thalassemia by measuring serum ferritin and to investigate the effects of iron chelation therapy including oral deferiprone and subcutaneous deferoxamine in the management of transfusion-related iron overload together with reproductive function. Methods: 90 female patients with thalassemia major (TM), thalassemia intermedia (TI) and thalassemia minor (T minor) were selected to investigate AMH by ELISA and ferritin by IRMA. Results: Serum AMH level was lower in female patients with transfusion dependent β-thalassemia than in T minor also, Ferritin was 25 fold more in TM compared to T minor (3088.0±2497.6 ng/ml vs. 120.3±36.2 ng/ml). There was significant negative correlation of AMH with ferritin in TM (r =-0.949; P<0.001*), in TI (r =-0.378; P =0.039*) and in T minor (r =-0.754; P<0.001*). The iron chelator, deferoxamine had significantly higher ferritin and lower AMH in TM and TI than deferiprone. Conclusion: the results demonstrated that females with TM and TI were found to have lower serum AMH levels than T minor and inversely related to the serum ferritin levels in all thalassemic groups. Also, it demonstrated that deferiprone was more efficient than deferoxamine in removing excess iron and reduced the deleterious effect of excess iron to the reproductive system, which leads to fertility preservation of female patients with transfusion–dependent β-thalassemia. Keywords: Anti-müllerian hormone, Ferritin, Iron overload, β-thalassemia, Deferoxamine, Deferiprone.